ANALISIS PERHITUNGAN DAN PELAPORAN PAJAK PENGHASILAN (PPh) DI P.T BANK SULUTGO - Utiarahman, Novlicia Putri; Tinangon, Jantje J.; Afandi, Dhullo (Universitas Sam Ratulangi, 2017)
Income tax is of the largest government revenue. Income Tax Law Article 4 Paragraph 2 gives a mandate to the government to impose income tax on certain earnings final. This study aims to determine how the calculation and report income taxÂ on savings, deposits, giro customer at PT. Bank SulutGo. Descriptive analysis was employed in this study. Data were obtained by field studies. The result shows that the calculation and reports income tax on savings, deposits, giro at PT. Bank SulutGo have compiled with the law of regulation. Leaders of PT. Bank SulutGo should improve the service guality to each customer, so that custumer can increase the amount of savings.Keywords : calculation, reporting, savings, deposits, giro